The Signing of the U.S.-India Agreement Concerning Peaceful Uses of Nuclear Energy - Jörn Müller (Göttingen Journal of International Law)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} p.MsoFootnoteText, li.MsoFootnoteText, div.MsoFootnoteText {mso-style-noshow:yes; margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:21.25pt; margin-bottom:.0001pt; text-align:justify; text-indent:-21.25pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} span.MsoFootnoteReference {mso-style-name:"Fußnotenzeichen,Footnote Reference 1a"; mso-style-noshow:yes; vertical-align:super;} p.ArticleText, li.ArticleText, div.ArticleText {mso-style-name:"Article Text"; mso-style-update:auto; margin:0cm; margin-bottom:.0001pt; text-align:justify; text-indent:1.0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} /* Page Definitions */ @page {mso-footnote-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") fs; mso-footnote-continuation-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") fcs; mso-endnote-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") es; mso-endnote-continuation-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") ecs;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 70.85pt 2.0cm 70.85pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> On 10 October 2008, the US Secretary of State Condoleezza Rice and the Indian Minister of External Affairs Pranab Mukherjee signed the “Agreement for Cooperation between the Government of the United States of America and the Government of India Concerning Peaceful Uses of Nuclear Energy” (hereafter: US-India Agreement).<!--[if !supportFootnotes]-->[1]<!--[endif]--> The text of the US-India Agreement had been agreed upon in summer 2007; the text was released on 3 August 2007. Preliminary assessments were mixed: Some scholars were highly critical, going so far as dubbing it a “debilitating blow to the non-proliferation regime”.<!--[if !supportFootnotes]-->[2]<!--[endif]--> Others saw the deal more favourably, pointing to a possible strengthening of the nuclear non-proliferation regime through a better integration of India.<!--[if !supportFootnotes]-->[3]<!--[endif]--> However, although the terms of the US-India Agreement have been known for some time, its impact depended on several other decisions that had to be made prior to its formal entry into force. In particular, India had to negotiate a safeguards agreement with the International Atomic Agency (IAEA). In addition, the Nuclear Suppliers Group (NSG) had to approve the US-India Agreement. Moreover, domestic approval both within India and the United States had to be reached. Several early commentators correctly pointed out that there was still room for possible modifications of the Agreement.<!--[if !supportFootnotes]-->[4]<!--[endif]--> Moreover, it was entirely possible that the Agreement would be defeated altogether.<!--[if !supportFootnotes]-->[5]<!--[endif]--> Now that all milestones have been reached and the Agreement has been formally concluded, this note will outline its background and its contents and give a brief assessment of its compatibility with and its impact on the international nuclear non-proliferation regime. The first part of the note will give a short overview of the international non-proliferation regime relevant for the US-India Agreement. The second part will deal with the evolution of the Agreement and will give some background information on the Indian nuclear program. The third part will give a preliminary assessment of the Agreement’s impact on the global non-proliferation regime. <!--[if !supportFootnotes]--> <!--[endif]--> <!--[if !supportFootnotes]-->[1]<!--[endif]--> The agreement is available in full text at http://www.state.gov/r/pa/prs/ps/2007/ aug/90050.htm (last visited 5 November 2008). It is also sometimes termed as “123 Agreement”, referring to section 123 of the US Atomic Energy Act of 1954, Pub. L. 109-401, 68 Stat. 919, which lays down the requirements under US domestic law for nuclear cooperation with other States. <!--[if !supportFootnotes]-->[2]<!--[endif]--> Kesav Murthy Wable, The U.S.-India Strategic Nuclear Partnership: A Debilitating Blow to the Non-Proliferation Regime, Brooklyn Journal of International Law 33 (2008) 719-759. <!--[if !supportFootnotes]-->[3]<!--[endif]--> Kate Heinzelman, Towards Common Interests and Responsibilities: The U.S.-India Civil Nuclear Deal and the International Nonproliferation Regime, Yale Journal of International Law 33 (2008) 447-478, 449. <!--[if !supportFootnotes]-->[4]<!--[endif]--> Id., 472-478; Oliver Meier, The US-India Nuclear Deal: The End of Universal Non-Proliferation Efforts?, Internationale Politik und Gesellschaft (2006) 4, 28-43, 38-41. <!--[if !supportFootnotes]-->[5]<!--[endif]--> Leonard Weiss, U.S.-India Nuclear Cooperation. Better Later than Sooner, Nonproliferation Review 14 (2007) 429-457, 452; Harald Müller & Carsten Rauch, Der Atomdeal. Die indisch-amerikanische Nuklearkooperation und ihre Auswirkung auf das globale Nichtverbreitungsregime (2007), 23. Especially domestic approval in India turned out to be difficult, yet was finally achieved in summer 2008.